Rice Bran’s Effect on Total Cholesterol, HDL, and LDL/HDL Ratio on Hypercholesterolemia Rats - Endin Nokik Stujanna; Sidhi Laksono Purwowiyoto; Wawang Setiawan Sukarya (Berkala Kedokteran, 2023)
Abstract: Hypercholesterolemia is a metabolism disorder characterized by increased or decreased lipid fraction in plasma. The of this research was to prove the effect of Rice bran to decrease of total Cholesterol rate, ratio of LDL / HDL and increase rate of HDL in hypercholesterolemia male white rats (Rattus norvegicus). The Research of the study was pure experiment by using post test randomized control design. Research Sample divided into five groups. The first group as a negative control, the second group as a positive control, and another groups were given rice brand, with various dose: 0,54 ml/a/day, 1,08 ml/a/day, 1,62 ml/a/day. The results of this research is rice brand can decrease of total cholesterol rate ( r2=0,964), decreased of ratio of LDL / HDL (r2=0,836), and increase of rate of HDL (r2=0,951) (ANOVA P=0,000). Rice bran can decrease total cholesterol rate, ratio of LDL / HDL and increase rate of HDL blood.